The Institutionalization of Accrual Accounting: The Perspective of New Institutional Sociology Theory (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This study aims to understand an accounting system change of a local government in Indonesia. This study is a qualitative and interpretive case study. Data collection is done through interviews of key actors who were involved in the process of accrual accounting institutionalization and documentation.The result of this study shows that the institutional isomorphism occurs on the implementation of accrual accounting at the local government. Coercive isomorphism are shown by the finding that the adoption of accrual accounting was affected by the central government, namely by issuing the regulations such as Government Regulation no. 71 of 2010 and Regulation of the Minister of Home Affairs no.64 of 2013. Normative isomorphism was found on the findings of consultant and academic involvement in the implementation of accrual accounting. Mimetic isomorphism was found when the local government conducted benchmarking to the other local governments that became the best practice in the accrual accounting implementation in Indonesia. In reality these three forms of institutional mechanism were interact each other, then contribute in influencing the practices and the actors during the accrual accounting institutionalization process in the local government.